KORELASI KEMAMPUAN TAHFIZHUL QUR’AN DENGAN HASIL MATA PELAJARAN AL-QUR’AN HADITS DI MTS MUHAMMADIYAH 2 PONDOK PESANTREN KARANGASEM PACIRAN LAMONGAN: KORELASI KEMAMPUAN TAHFIZHUL QUR’AN DENGAN HASIL MATA PELAJARAN AL-QUR’AN HADITS DI MTS MUHAMMADIYAH 2 PONDOK PESANTREN KARANGASEM PACIRAN LAMONGAN - Yusuf Wibisono (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2024)
This study aims to determine the correlation between the ability of Tahfizhul Qur'an with the results of Al-qur'an Hadith subjects at MTS Muhammadiyah 2 Pondok Karangasem Paciran. In this study, researchers used a survey method with a correlational approach which was carried out at MTS Muhammadiyah 2 Pondok Karangasem Paciran by involving class VIIIB students. Data was collected by means of observation, interviews, questionnaires and documentary studies. The results obtained to answer the problem formulation are: (1) How is the level of ability to memorize the Qur'an of class VIII B female students of MTs Muhammadiyah 2 Karangasem Paciran?, (2) How is the level of Al-Qur'an Hadith learning achievement for female students of class VIII B of MTs Muhammadiyah 2 Karangasem Paciran?, (3) Is there a positive relationship between the ability to memorize the Qur'an and learning achievement of Al-Qur'an Hadith for female students of class VIII B of MTs Muhammadiyah 2 Karangasem Paciran ?. From the results of the study it was found that: There is a positive correlation between the ability of tahfidz Al Qur'an and the learning outcomes of class VIII B students of MTs Muhammadiyah Paciran Lamongan with the calculation of the correlation coefficient (rcount) which is obtained a value of 0.738, then the value is compared with at the level of 5% significant for N = 14 and df = N – 2 = 14 – 2 = 12 the number is 0.532 and it can be seen that is greater than or 0, > 0.532, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted . The level of correlation or relationship between the ability of tahfidz Al-Qur'an and the learning outcomes of class VIII B students of MTs Muhammadiyah Paciran Lamongan is included in the "strong" category, namely by looking at the product moment correlation results will be obtained a value of 0.738 which if interpreted lies in the moderate or adequate category with limit value 0.70 - 0.90 which means the relationship between the variables X and Y has a strong correlation.